DETERMINATION OF CHARACTERISTICS OF NEWLY DISCOVERED ECLIPSING BINARY 2MASS J18024395 +4003309 = VSX J180243.9+400331 - Andronov, I. L.; Breus, V. V.; Zola, S. (Одеські астрономічні публікації, 2012)
During processing the observations of the intermediate polar 1RXS J180340.0+401214, obtained 26.05.2012 at the 60-cm telescope of the Mt. Suhora observatory (Krakow, Poland), variability of 2MASS J18024395 +4003309 was discovered. As this object was not listed in the "General Catalogue of Variale Stars" or "Variable Stars Index", we registered it as VSX J180243.9+400331. Additionally we used 189 separate observations from the Catalina Sky Survey spread over 7 years. The periodogram analysis yields the period of 0d.3348837±0d.0000002. The object was classified as the Algol-type eclipsing binary with a strong effect of ellipticity. The depths of the primary and secondary minima are nearly identical, which corresponds to a brightness (and maybe) mass ratio close to 1. The statistically optimal degree of the trigonometric polynomial n=4. The most recent minimum occurred at HJD 2456074.4904. The brightness range from our data is 16.56-17.52 (V), 16.18-17.08 (R). The NAV ("New Algol Variable") algorithm was applied for statistically optimal phenomenological modeling and determination of corresponding parameters.